Bio-Hybrid Micro/Nanodevices Powered by Flagellar Motor: Challenges and Strategies - Kim, Jin-Woo; Tung, Steve (Frontiers in Bioengineering and Biotechnology, 2015)
Molecular motors, which are precision-engineered by nature, offer exciting possibilities for bio-hybrid engineered systems. They could enable real applications ranging from micro/nano fluidics, to biosensing, to medical diagnoses. This review describes the fundamental biological insights and fascinating potentials of these remarkable sensing and actuation machines, in particular bacterial flagellar motors, as well as their engineering perspectives with regard to applications in bio-engineered hybrid systems and nanobiotechnology.